An executive's guide to information technology principles, business models, and terminology - Plant, Robert T.; Murrell, Stephen (Cambridge University Press, 2007)
Assessing the most valuable technology for an organization is becoming a growing challenge for business professionals confronted with an expanding array of options. This 2007 book is an A-Z compendium of technological terms written for the non-technical executive, allowing quick identification of what the term is and why it is significant. This is more than a dictionary - it is a concise review of the most important aspects of information technology from a business perspective: the major advantages, disadvantages and business value propositions of each term are discussed, as well as sources for further reading, and cross-referencing with other terms where applicable. The essential elements of each concept are covered in a succinct manner so the reader can quickly obtain the required knowledge without wading through exhaustive descriptions. With over 200 terms, this is a valuable reference for non- and semi-technical managers, executives and graduate students in business and technology management